2020
DOI: 10.1002/oby.22855
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Dietary Ketone Ester Decreases Body Weight and Adiposity in Mice Housed at Thermoneutrality

Abstract: The aim of this study was to examine the effects of a ketone ester (KE)-supplemented diet on energy expenditure (EE) and adiposity in mice housed at 23 °C versus thermoneutrality (30 °C), in which sympathetic nervous system activity is diminished. Methods: Thirty-two 10-week-old male C57BL/6J mice were assigned to 1 of 4 groups (n = 8 per group): 30% KE diet + 23 °C (KE23), control (CON) diet + 23 °C (CON23), 30% KE diet + 30 °C (KE30), or CON diet + 30 °C (CON30). CON mice were pair-fed to the average intake … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…We found mice consuming a KE diet remained weight stable, with no changes in FM or LBM, yet the control group increased body weight and fat mass over the course of the study. There were no differences in energy intake between the groups, which agrees with our previous findings in juvenile mice ( 19 ). Interestingly, the KE group displayed a unique skeletal muscle transcriptional and proteomic profile compared to the control group yet had a very similar lipidomic profile.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found mice consuming a KE diet remained weight stable, with no changes in FM or LBM, yet the control group increased body weight and fat mass over the course of the study. There were no differences in energy intake between the groups, which agrees with our previous findings in juvenile mice ( 19 ). Interestingly, the KE group displayed a unique skeletal muscle transcriptional and proteomic profile compared to the control group yet had a very similar lipidomic profile.…”
Section: Discussionsupporting
confidence: 92%
“…In human clinical trials, circulating ketones such as β-HB reach levels ranging from 1 to 2 mM/L and up to 5 mM/L ( 6 , 84 , 85 ). Comparatively, we (and others) have shown the ability to induce similar levels of ketones in rodents ( 15 , 17 , 19 , 86 ). Exogenous ketones offer a way to induce ketone production quickly and efficiently in humans without the need for caloric restriction or a KD and have been well-studied in exercise physiology ( 11 , 12 , 87 89 ).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Animal state of ketosis was evaluated via whole blood D-βHB (Keto-MoJo blood ketone meter; Keto-Mojo, Napa, CA, USA) concentrations 86 . Tail vein puncture was used for blood sample, which was tested on day 0 pre-PPE exposure, and then 1- and 2-weeks following AAA induction.…”
Section: Methodsmentioning
confidence: 99%
“…First of all, d-3HB was shown to be able to improve the blood lipid profile in obese adults by a reduction in lowdensity lipoprotein (LDL) cholesterol, increase in highdensity lipoprotein (HDL) cholesterol, smaller adipocyte cell volume, and inhibition of lipolysis via a G-protein-coupled receptor (GPCR) which reduced subsequent release of serum lipolytic products (Caminhotto et al 2017). At the cellular level, d-3HB markedly increased mitochondrial uncoupling in brown adipose tissue (BAT) which increased mitochondrial respiration and thermogenesis, thereby results in increased resting energy expenditure (REE) in the obese (Deemer et al 2020;Walton et al 2020). More recently, studies revealed that the anti-inflammatory actions of d-3HB on the NOD-like receptor pyrin-domain containing 3 (NLRP3) inflammasome in obese adults can also prevent obesity and associated cardiometabolic complications such as atherosclerosis (Neudorf et al 2020;Zhang et al 2021).…”
Section: D-3hb and Cardiometabolic Healthmentioning
confidence: 99%